Pseudomonas aeruginosa-derived metabolites and volatile organic compounds: impact on lung epithelial homeostasis and mucosal immune response - Kuo, Shanny Hsuan; Lau, Gee W. (Frontiers in Immunology, 2025)
Pulmonary diseases, such as cystic fibrosis (CF), chronic obstructive pulmonary disease (COPD), and ventilator-associated pneumonia (VAP), are attributed to the prolonged infection of the airway and hypersecretion of mucus. Pseudomonas aeruginosa (PA) is one of the most common nosocomial pathogens in these diseased airways, secreting a wide spectrum of metabolites and volatile organic compounds (VOCs) that significantly impact the respiratory epithelium, including disruption of mucus homeostasis and inflammatory responses of the diseased lungs. In this review, we highlighted the major metabolites and VOCs produced by PA and the mechanisms by which they modulate inflammation, cellular injury, and mucus hypersecretion in respiratory epithelium.